INDONESIA’S RESPONSIBILITY FOR CORAL REEF DAMAGE IN KEPULAUAN SERIBU - Natalia Yeti Puspita; Tisa Windayani; A. Aris Swantoro (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2013)
Coral reef is an underwater biodiversity great in value. Sovereignty of the state to explore its natural resources is deeply recognized by international law. On the other hand, the state must also guaranteethe preservation of its natural resources. This research will explain about state responsibility (Indonesia)upon the damage of the coral reefs based on Convention on Biodiversity in Kepulauan Seribu. Terumbu karang merupakan salah satu kekayaan laut yang sangat tinggi nilainya. Hukum internasional mengatur bahwa meskipun suatu negara berdaulat penuh atas wilayahnya, negara tersebut berkewajibanuntuk tidak merusak lingkungan. Penelitian ini menganalisis mengenai tanggung jawab Indonesia sebagainegara peratifikasi Konvensi Keanekaragaman Hayati 1992 sehubungan dengan kerusakan terumbu karang di Kepulauan Seribu.